2004
DOI: 10.1242/jcs.01484
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PrPSc formation by lentiviral gene transfer of PrP containing dominant negative mutations

Abstract: Currently, there is no treatment to cure transmissible spongiform encephalopathies. By taking advantage of the `prion-resistant' polymorphisms Q171R and E219K that naturally exist in sheep and humans, respectively, we have evaluated a therapeutic approach of lentiviral gene transfer. Here, we show that VSV-G (vesicular stomatitis virus G glycoprotein) pseudotyped FIV-(feline immunodeficiency virus) derived vectors carrying the mouse Prnp gene in which these mutations have been inserted, are able to inhibit pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…This resistance was also maintained following active immunization against misfolded prion protein antigens. In other words, it persisted, even after the scrapie pathogens had been transmitted/acquired either via intracerebral inoculation or via transfusion of blood derived from asymptomatic infected carriers (Crozet et al 2004, Criado et al 2005, Crecelius et al 2008. In turn, the non-transgenic mice represented the control disease models for scrapie etiopathology (wild-type prion model mice).…”
Section: Perspectives Of Somatic Cell Cloning and Transgenesis Of Farmentioning
confidence: 99%
“…This resistance was also maintained following active immunization against misfolded prion protein antigens. In other words, it persisted, even after the scrapie pathogens had been transmitted/acquired either via intracerebral inoculation or via transfusion of blood derived from asymptomatic infected carriers (Crozet et al 2004, Criado et al 2005, Crecelius et al 2008. In turn, the non-transgenic mice represented the control disease models for scrapie etiopathology (wild-type prion model mice).…”
Section: Perspectives Of Somatic Cell Cloning and Transgenesis Of Farmentioning
confidence: 99%
“…[96][97][98][99][100][101][102][103][104][105] These polymorphisms clearly restrict the range of conformations accessible to the prion and therefore its ability to replicate certain variants. 31,43,[106][107][108][109][110] However, many of the same sequence changes also function as dominant inhibitors of prion propagation in vivo, 105,[111][112][113][114][115][116][117][118] and a similar effect occurs upon co-expression of PrP homologues from different species. 79,[119][120][121][122][123][124] Thus, these sequence variants must target crucial events in prion propagation by the wildtype protein, and elucidating their mechanisms of action could be instructive for developing therapeutic interventions for these diseases.…”
Section: Balancing Aggregate Assembly and Disassembly Pathwaysmentioning
confidence: 99%
“…79,[119][120][121][122][123][124] Thus, these sequence variants must target crucial events in prion propagation by the wildtype protein, and elucidating their mechanisms of action could be instructive for developing therapeutic interventions for these diseases. [114][115][116] Early models suggested that PrP dominant-negative mutants acted by titrating away a host-encoded cofactor (protein X) required for the conversion reaction; 122 however, these sequence variants also inhibit prion propagation in cell-free systems, suggesting that their effects are mediated directly through prion-prion interactions. [125][126][127] In this scenario, PrP sequence variants would interact with the templating surface on an aggregate and either slow, as has been proposed for a Q219K variant, or block, as has been ©2 0 1 1 L a n d e s B i o s c i e n c e .…”
Section: Balancing Aggregate Assembly and Disassembly Pathwaysmentioning
confidence: 99%
“…Importantly, these studies also showed that introduction of a heterologous PrP C can dramatically inhibit the conversion of the endogenous PrP C . This led to the notion of a dominant negative effect, a process by which expression of a heterologous PrP C can block in trans the conversion of the wild type PrP C in infected cultures [35,56,64,110] or in mice [103]. Although the mechanisms by which the interaction between heterologous PrP C and PrP Sc can impair prion infection are not fully understood [57,117], experiments conducted with infected N2a cells have shown that lentiviral transduction of heterologous PrP C can inhibit PrP Sc formation [35].…”
Section: Prp C Polymorphisms Amino Acid Substitution and Prion Propmentioning
confidence: 99%